A criança com cegueira congênita na escola: uma análise da mediação de conceitos - Paulino, Vanessa Cristina (2010)
Children grasp information through several senses: touch, sight, smell, taste, and kinesthetic, among them the vision can be considered one of the most important for the acquisition of rich information and less time as well as responsible for the integration of different sensory content. We agree that children with blindness due to the absence of a sensory channel, must have an education that enhances their chances of understanding the world, so do not present conceptual inconsistencies identified in research on the topic. Consistent with these notes aim with this study to analyze the characteristics used by students with congenital blindness in the definition of concepts in the classroom as well as identify which learning contexts were crucial to the meanings. The study included three students with congenital blindness, without other sensory impairments, enrolled in the first cycle of basic education and their regular teachers common. In order to achieve the stated objectives of the Protocol was drafted Observation Activities and Teaching Strategies, which guided the activities record and Detailing of Framework Concepts, which supported the analysis and categorization of data. In addition, interviews were held for the Characterization of Participants - students (A, B and C) and teachers (PA, PB, PC) and applied the questionnaire in Brazil Economic Classification Criterion, those responsible for students. For the analysis of the concepts covered in class, each was categorized as to: Level Approach (primary, secondary or tertiary), Predominant Characteristics, Sensory Attributes / Access and Context of Reference (daily life, school or daily life / school). The results indicated that the conceptual definitions of the participant were based mainly on features related to function (21%) of the concepts and tactile attributes / experience (31%), the participant B was based on the action (38%) of the concepts and auditory attributes / description (20%) and participating in the function C (27%) questioned the concepts and attributes in hearing / description (31%). It is noteworthy that among the three participants in the olfactory and gustatory sensory attributes were not mentioned although they are important resources for obtaining information. With respect to the context of reference, the participant noted the context in daily life situations and 28% of the school at 7%, in other not reported, the participant quoted the daily context B in 40% of their responses and 15% in school, and participant pointed to the daily life context C in 24% of inquiries and 23% in the school context. These results indicate that even when the concepts had been asked tackled primary classroom were related to appropriate information in previous school settings and / or in everyday life. It was also among the participants, mistakes or deviations regarding the conceptual contents that had been made possible in schools, so in addition to motivating environments, educators and family members should assess the understanding of children with blindness in regard to information. Consistently raised the questions that this research concludes that, although it is not possible to generalize their results, that provided information relevant to both parents and for educators regarding the pathways to learning for children with blindness, and provided important , the new studies that suggest strategies that can be used in the context of regular classroom policy, which favors an education for EVERYONE, and to consider the specific learning of students with blindness.